2021
DOI: 10.1136/oemed-2021-107628
|View full text |Cite
|
Sign up to set email alerts
|

Risks of COVID-19 by occupation in NHS workers in England

Abstract: ObjectiveTo quantify occupational risks of COVID-19 among healthcare staff during the first wave (9 March 2020–31 July 2020) of the pandemic in England.MethodsWe used pseudonymised data on 902 813 individuals employed by 191 National Health Service trusts to explore demographic and occupational risk factors for sickness absence ascribed to COVID-19 (n=92 880). We estimated ORs by multivariable logistic regression.ResultsWith adjustment for employing trust, demographic characteristics and previous frequency of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 7 publications
4
39
0
3
Order By: Relevance
“…The results obtained indicate that working in the health sector during the COVID-19 pandemic in Mexico constituted a greater risk of infection and death. These data are consistent with those reported by Van der Plaat et al [35], who found that HCWs who worked with infected patients had a higher risk of infection than HCWs who did not have direct contact with COVID-19 patients did.…”
Section: Discussionsupporting
confidence: 93%
“…The results obtained indicate that working in the health sector during the COVID-19 pandemic in Mexico constituted a greater risk of infection and death. These data are consistent with those reported by Van der Plaat et al [35], who found that HCWs who worked with infected patients had a higher risk of infection than HCWs who did not have direct contact with COVID-19 patients did.…”
Section: Discussionsupporting
confidence: 93%
“…Long-term contact exclusively with COVID-19 patients, as well as the possibility of losing attention and non-compliance with protection measures, may have caused the highest prevalence of positive staff in COVID hospital. Higher seroprevalence among personnel delivering direct care to COVID-19 patients than among those with lower exposure has been observed in other studies, [17] , [18] . However, SARS-CoV-2 antibody prevalence among HCWs in the COVID dedicated hospital was lower than the prevalence in the Spanish referral hospital obtained at the beginning of the pandemic, during the peak of the first wave [19] , but higher than overall seroprevalence among more than 6 thousand employees in 17 hospitals in this country [20] .…”
Section: Discussionsupporting
confidence: 67%
“…In the context of the current COVID-19 pandemic, dental treatment is stressful for both patients and dental healthcare professionals [10][11][12]. By using the "KS system," dentists may lower the transmission of aerosol infections and reduce the stress and anxiety of potentially contracting an infection during dental procedures.…”
Section: Discussionmentioning
confidence: 99%